Model Pemberdayaan Ekonomi Dan Sosial Masyarakat Berbasis Masjid Kampus Surabaya (Studi Kasus Pada Masjid Kampus Unair, Its Dan Unesa) - Mukhtar Adinugroho; Teguh Herlambang; Riyan Sisiawan Putra; Mohamad Rijal Iskandar Zhulqurnain (ITB AAS INDONESIA Surakarta, 2023)
Mosque-based community empowerment is a da'wah movement to increase the independence and welfare of the community. Mosques as religious institutions are expected to be able to prosper society with productive programs through the concept of community empowerment in the economic and social fields. Based on these reasons, this study aims to find a campus mosque-based community empowerment model from the economic and social aspects. This study uses a qualitative approach with a case study method with pattern matching analysis techniques. Data collection used a criteria technique to determine informants who totaled 5 takmir in three mosques, namely, Manarul '11mi ITS Mosque, Ulul 'Azmi Unair Mosque, and Baitul Makmur Unesa Mosque to be interviewed in depth, observed, and documented. The results of this study found that every mosque has enormous potential in empowering the socio-economic community, but it has not been optimal in its implementation so that the congregation and the wider community do not feel the impact of the presence of the mosque. This is also due to the lack of professional experts in mosque management. The combination of the three campus mosques produces a mosque-based economic and social-community empowerment model that can be implemented in mosques that wish to empower the community economically and socially. If a mosque wants to do empowerment, it is required to collaborate with the government, universities, the community, and the private sector. Mosques must implement modern administration and be able to identify community potential. Inputs to economic empowerment include institutions, leadership and goals. The process of economic and social empowerment includes spiritual formation, personal mental formation, capacity building, and empowering. The output of economic-social empowerment includes character strengthening, mental character strengthening, emotional relationship strengthening, business strengthening and economic-social strengthening. The outcomes obtained include spiritual abilities, economic abilities and social abilities so that they are able to give birth to world and hereafter welfare. Thus the mosque is not only prospered by the community, but the mosque is able to prosper the community.